Cálculo da tensão nos sólidos para o espessamento e filtração de carbonato de cálcio em suspensões de fluidos newtonianos e pseudoplásticos - Oliveira Júnior, Hélio de (2014)
The study of the filtration and thickening of particulate systems are used in many industrial processes that involve processes of solid-liquid separation, such as settling, filters, tanks, in the drilling of oil wells, among others. This paper aims to move forward in the empirical mechanisms involved in the processes of solid-liquid separation and to obtain constitutive equations that relate the pressure and permeability in porous solids from fluids Newtonian and non-Newtonian media, studying the process of sediment compaction in non-Newtonian fluids and constitutive equations to obtain high pressures in the solids. Aqueous solutions of xanthan gum concentration of 0.1% by weight were used in the experiments, in order to ensure a non-Newtonian solution. For the preparation of suspensions, was used as calcium carbonate particulate material in the separation process involved an initial concentration of 11 to 12% by volume. The settling tests were carried to term and the resulting pellets from each assay were evaluated by using the attenuation technique Gamma (TARG) which is a non-destructive technique based on measuring the attenuation of gamma rays. The concentrated sediment and remained stable between 30 and 48% by volume. Assays were performed at high pressures in a commercial HTHP filter type with a capacity of 400 ml, where suspension concentration used was 5% by volume. The results show that TARG was effective in determining sediment concentration distributions formed from Newtonian and non-Newtonian solutions, allowing for constitutive equations to obtain the solids pressure, permeability of the porous medium as well as to obtain the distribution of compaction of the sediment as a function of position and time, showing that sedimentation behavior of Newtonian and non-Newtonian fluid exhibit similar concentration distribution of solids settling time already quite distinct.